Structural, Elastic, and Electronic Properties of Antiperovskite Chromium-Based Carbides ACCr3 (A = Al and Ga) - D. F. Shao; W. J. Lu; S. Lin; P. Tong; Y. P. Sun (Advances in Condensed Matter Physics)
We theoretically investigated antiperovskite chromium-based carbides ACCr3 through the first-principles calculation based on density functional theory (DFT). The structure optimization shows that the lattice parameter of ACCr3 is basically proportional to the radius of A-site elements. The calculated formation energies show that AlCCr3 and GaCCr3 can be synthesized at ambient pressure and are stable with nonmagnetic ground states. Based on the calculation of elastic constants, some elastic, mechanical, and thermal parameters are derived and discussed. AlCCr3 and GaCCr3 show ductile natures and may have similar thermal properties. From the analysis of the electronic structures, it was found that there are electron and hole bands that cross the Fermi level for AlCCr3 and GaCCr3, indicating multiple-band natures. The Fermi level locates at the vicinity of the density of states (DOSs) peak, which leads to a large DOS at Fermi level dominated by Cr-3d electrons. The band structures of AlCCr3 and GaCCr3 are very similar to those of the superconducting antiperovskite MgCNi3. The similarity may make AlCCr3 and GaCCr3 behave superconductively, which needs to be further investigated in theoretical and experimental studies.